The Characters’ Values of Barongan Turonggo Laras Arts in Kendal Regency - Desnatia Munzilatul Qur'aniyah; Muhammad Jazuli; Wahyu Lestari (Universitas Negeri Semarang, 2023)
Barongan art is folk art that has been adhered to people's lives. Its presence is used as entertainment. Barongan art not only functions as entertainment but contains character values in the elements of the performance. The purpose of this research is to describe the form and character values of barongan turonggo laras art performance. The method used in the research is a qualitative method with phenomenological, ethical, and emic approaches. The data collection techniques used are observation, interviews, and documentation. The data validity technique used is the triangulation technique. The data were analyzed using the stages of data reduction, presentation, and conclusion. The results show that the barongan turonggo laras art developed in Galih Village, Gemuh District, Kendal Regency has eight characters’ values, namely: 1) Religious, 2) Honesty, 3) Tolerance, 4) Hard work, 5) Creativity, 6) Love for the country, 7) Responsibility, and 8) Cooperation. The cultivation of character values in barongan turonggo laras art can be analyzed through performance elements consisting of movement, dancers, dance music, makeup, fashion, time, place, stage, sound, lighting, properties, and audience. For example, it provides an understanding to members and the community about the values contained in the elements of the barongan turonggo laras art performance, such as the values contained in movements have a religious value shown in sembahan movements and the floor pattern elements contain the value of tolerance that occurs between fellow dancers.